2002
DOI: 10.1577/1548-8659(2002)131<0507:hamols>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and Movement of Lake Sturgeon in the Upper Mississippi River System, USA

Abstract: Lake sturgeon Acipenser fluvescens, which are now protected from harvest, are considered rare in the upper Mississippi River and little information is available on the remaining populations. Transmitters were implanted into 31 lake sturgeon from two sites in the upper Mississippi River to describe their habitats and movement. The areas surrounding the tagging sites were core areas for both groups of lake sturgeon based on the high use (about 50% of locations by group) and frequent return to these areas by many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 16 publications
8
96
1
Order By: Relevance
“…Results of the four-year study also indicated that most lake sturgeon exhibit site fidelity; although they frequently make localized movements, they demonstrated a preference for certain areas (Barth and Ambrose 2006). Borkholder et al (2002) and Knights et al (2002) have documented similar findings.…”
Section: Movements/dispersalsupporting
confidence: 54%
“…Results of the four-year study also indicated that most lake sturgeon exhibit site fidelity; although they frequently make localized movements, they demonstrated a preference for certain areas (Barth and Ambrose 2006). Borkholder et al (2002) and Knights et al (2002) have documented similar findings.…”
Section: Movements/dispersalsupporting
confidence: 54%
“…Duration of holding ranged from 44 to 199 days. Extended periods of inactivity and restricted movement in discrete areas have been documented for several sturgeon species (Wooley and Crateau 1985; Kieffer and Kynard 1993;Moser and Ross 1995;Foster and Clugston 1997;Erickson et al 2002;Knights et al 2002). Gulf sturgeon did not move further than 0.6 km from holding sites (Foster and Clugston 1997).…”
Section: Houstonmentioning
confidence: 81%
“…While movement patterns of adult lake sturgeon have been described for a variety of systems (e.g., Fortin et al 1993;Rusak and Mosindy 1997;McKinley et al 1998;Auer 1999b;Knights et al 2002), movement data on age-0 juveniles is less complete and has only been generated for large (>220 mm) fish using radio telemetry (Holtgren and Auer 2004;Benson et al 2005a). Utilizing markrecapture data would allow movement patterns of smaller (50 -220 mm) age-0 juveniles to be described.…”
Section: Introductionmentioning
confidence: 99%